Epibiont Assemblages on Nesting Hawksbill Turtles Show Site-Specificity in the Persian Gulf - Loghmannia, Javad; Nasrolahi, Ali; Rezaie-Atagholipour, Mohsen; Kiabi, Bahram H. (Frontiers in Ecology and Evolution, 2021)
The study of epibiont communities living on sea turtles could be considered as a low-cost approach to provide valuable insights into the habitat use and immigration behavior of these threatened marine reptiles. It has been, however, neglected in many regions. We examined epibiont assemblages of 46 hawksbill turtles (Eretmochelys imbricata) from two relatively distinct nesting sites in the Persian Gulf. These include 28 turtles from Dayyer-Nakhiloo National Park (DNNP) at the northern Gulf characterized by the Gulf environmental extremes (high salinities and wide-ranging temperatures), and 18 turtles from the Shibderaz beach at the Strait of Hormuz with a more moderate environment exposed by incoming currents from the Gulf of Oman. A total of 54 epibiont taxa were identified on the body surface of the turtles, 46 taxa from Shibderaz and 29 taxa from DNNP. Two barnacle species, Chelonibia testudinaria and Platylepas hexastylos, along with harpacticoid copepods and Rotaliid foraminifers were the most frequent epibionts, observed on almost all examined turtles. Harpacticoids were the most abundant epizoic taxa by the number (19.55 ± 3.9 ind.9 cm-2) followed by forams (Quinqueloculina spp.: 6.25 ± 1.5 and Rotaliids: 6.02 ± 1.3 ind.9 cm-2). Our results showed that the composition and structure of turtle epibionts in the two studied sites were significantly different with higher diversity at Shibderaz. We speculate that the difference is largely driven by their environmental conditions they live in. These baseline data are critical to adopt proper conservation and management strategies for this species in the harsh environment of the Gulf especially in the course of climate change. The data can further be used in regular monitoring studies to track ecological changes in this anthropogenically-impacted water body.